STUDENTS’ PERCEPTION OF THE USE OF DESCRIPTIVE TEXT IN INCREASING VOCABULARY AT SEVENTH GRADE OF SMP NEGERI 2 HILIDUHO - Telaumbanua, Syukur Prima; Harefa, Trisman; Maruao, Nursayani; Riswan Zega (Universitas PGRI Palembang, 2025)
This study investigates students’ perceptions of using descriptive texts to improve English vocabulary acquisition at SMP Negeri 2 Hiliduho. Motivated by students’ limited vocabulary mastery, which hinders their comprehension and writing of descriptive texts, the research employs a descriptive qualitative approach involving seventh-grade participants. Data were collected through questionnaires, interviews, and documentation. The findings reveal that descriptive texts provide meaningful context, aiding students in understanding and retaining new vocabulary. The inclusion of media such as images and videos further supports vocabulary learning by enhancing engagement and comprehension. Despite these benefits, challenges persist, including low motivation, repetitive instructional methods, and insufficient use of media, which limit students’ ability to relate new vocabulary to real-life contexts. Nevertheless, students expressed generally positive perceptions, noting that descriptive texts made learning more interactive, enjoyable, and useful for vocabulary development and writing improvement. The study recommends that teachers regularly integrate descriptive texts with visual aids and interactive strategies to foster greater student motivation and participation. These findings contribute to the advancement of more effective and engaging English language teaching practices at the junior high school level.